PERIODIC TABLE OF ELEMENTS - Kurbanbayeva, Saodat Khudabergan qizi (Educational Research in Universal Sciences, 2023)
The purpose of explaining the topic “Periodic Table of Elements” is to deepen students’ understanding of chemistry through this topic, that is, all living and non-living objects in nature are made up of 118 elements in the periodic table and in the periodic system of elementsinformation about the periodic relationships between the elements and the scientists who tried to explain them will be highlighted.